Efficacy of iguratimod vs. salazosulfapyridine as the first-line csDMARD for rheumatoid arthritis. Issue 2 (3rd March 2020) - Nozaki, Yuji; Inoue, Asuka; Kinoshita, Koji; Funauchi, Masanori; Matsumura, Itaru
Abstract: Objectives: We retrospectively evaluated the retention rate and clinical responses following treatment for rheumatoid arthritis (RA) with iguratimod (IGU) vs. salazosulfapyridine (SASP) as the first-line conventional synthetic disease-modifying antirheumatic drug (csDMARD). Methods: We analyzed 197 RA patients who were treated with IGU or SASP as the initial treatment in the 3-year study period. The retention rate, clinical response, the dosage and percent user of prednisolone (PSL), and safety profiles were evaluated. Results: At month 36, the retention rates of the IGU and SASP groups were 52.4 vs. 32.1%. The rate of responders (good or moderate response) at month 36 was 85.8 vs. 65.2% in the IGU and SASP groups, respectively. At month 36 for the IGU and SASP groups, the percentages of PSL users were 16.7 vs. 46.7%, and the PSL dosage was 0.3 mg/d vs. 2.0 mg/d, respectively. The cumulative rates of any adverse event (AE) at month 36 were 19.8 vs. 29.2% in the IGU and SASP groups, respectively. Conclusion: IGU is a useful first-line csDMARD treatment for RA patients, showing a high retention rate and good efficacy without an increased risk of serious AEs, including serious infections. Our findings also indicate a PSL dose-sparing effect of IGU treatment.